Executive Committee Minutes 2019-04-25 - Academic Senate:::::::::
Agenda – Approved. Minutes of 4/11/19 – Approved. Chair Report. President Report. Provost Report. Statewide Senator Report. Vice Chair Report. Vice President for Student Affairs Report. From SAC: Revised SAC Charge - approved as business for the Senate agenda. Vice President of Administration and Finance Report. Associated Students Report. Info Item: Library Archives Policy revision. From S&F: Carryover business – endorsed by the Ex Com. From EPC: Minimal Revision to AMCS – approved for Senate consent calendar. From EPC: Revision to Business Administration Minor AMCS – approved for Senate consent calendar. From APARC: Strategic Priorities for AY 19-20 approved as business for the Senate agenda. APARC Report. EPC Report. FSAC Report. CFA Report. Senate Agenda approved. Good of the Order.